Benelux countries’ security strategies: between europeanism and atlanticism - Anastasia A. Posazhennikova (Научно-аналитический вестник Института Европы РАН)
In the article, transformation of the foreign policy and security strategies of the Benelux countries – Belgium, the Netherlands and Luxembourg – is analyzed against the exacerbating conflict in Ukraine. Using the comparative historical method, we outline the evolution of strategic trends of Europeanism – seeking deeper integration within the European institutional framework – and Atlanticism – pursuing a general strategic orientation towards the United States – in the three countries. As smaller-sized countries, they initially combined Europeanism and «moderate» Atlanticism, which left them some space for foreign policy maneuver. Since the 1990s, the Dutch foreign policy more closely follows the Atlanticist paradigm, while those of Belgium and Luxembourg are characterized more by Europeanism. The analysis of the EU strategic autonomy debate as a case study has shown that Belgium, the Netherlands and Luxembourg seek the greatest possible economic benefits from the autonomy initiatives. Besides, the balance between the strategic trends remains; Belgium and Luxembourg positively view deeper EU defense cooperation, while the Netherlands mostly sees security guarantees in Euro-Atlantic cooperation. The current state in European security has thus not fundamentally changed the Benelux countries’ approaches to balancing Europeanism and Atlanticism that have been characteristic for them since the 1990s. Besides, for Belgium, support for deeper integration has become a key identity feature, while the Netherlands relies on special relations with the United States and ad hoc coalitions in the EU; Luxembourg’s foreign policy can be described to follow a free rider strategy.